Hubungan kebiasaan konsumsi kopi dengan kejadian prehipertensi pada mahasiswa preklinik Fakultas Kedokteran Universitas Palangka Raya - Kamilan, Sofya; Jelita, Helena; Ahmad, Farah Fauziyah Radhiyatulqalbi; Lestarisa, Trilianty; Kahanjak, Donna Novina (Barigas: Jurnal Riset Mahasiswa, 2024)
Over time, there is a decrease in body resistance in a number of individuals, leading to the emergence of health problems. A common phenomenon observed is hypertension, which is often referred to as "the silent killer". Prehypertension is a person's blood pressure above the normal range but has not reached the degree of hypertension. One factor that is thought to increase the risk of hypertension is coffee consumption. Coffee contains caffeine which is a stimulant substance that can increase alertness, speed up heart rate, and increase blood pressure. This study aims to determine the coffee consumption habits of FK UPR preclinical students, determine the blood pressure of FK UPR preclinical students and classify individuals as prehypertensive and non-prehypertensive, analyze the relationship between coffee consumption habits and the incidence of prehypertension. Observational research method with cross-sectional research design. The sample was obtained using Proportionate Stratified Random Sampling with a sample number of 81 respondents. The statistical analysis used in this study was the chi-square test. The results showed that of the 81 respondents, the majority had the habit of drinking coffee, were experiencing prehypertension (120-139 mmHg / 80-89 mmHg). Based on the results of the chi-square statistical test conducted in this study, p-value = 0.033 (p<0.05) was obtained which stated that there was a relationship between coffee consumption habits and the incidence of prehypertension in preklink students of the Faculty of Medicine, University of Palangka Raya. There is a relationship between coffee consumption habits and the incidence of prehypertension in preklink students of the Faculty of Medicine, University of Palangka Raya.